Restoring antiviral immunity with adoptive transfer of ex-vivo generated T cells. Issue 6 (November 2018) - Migliori, Edoardo; Chang, Mark; Muranski, Pawel
Abstract : Purpose of review: Latent viruses such as cytomegalovirus (CMV), Epstein–Barr virus (EBV) and adenovirus (ADV) often reactivate in immunocompromised patients, contributing to poor clinical outcomes. A rapid reconstitution of antiviral responses via adoptive transfer of virus-specific T cells (VSTs) can prevent or eradicate even refractory infections. Here, we evaluate this strategy and the associated methodological, manufacturing and clinical advances. Recent findings: From the early pioneering but cumbersome efforts to isolate CMV-specific T cell clones, new approaches and techniques have been developed to provide quicker, safer and broader-aimed ex-vivo antigen-specific cells. New manufacturing strategies, such as the use of G-Rex flasks or 'priming' with a library of overlapping viral peptides, allow for culturing greater numbers of cells that could be patient-specific or stored in cell banks for off-the-shelf applications. Rapid isolation of T cells using major histocompatibility complex tetramer or cytokine capture approaches, or genetic reprogramming of cells to target viral antigens can accelerate the generation of potent cellular products. Summary: Advances in the ex-vivo generation of VSTs in academic medical centres and as off-the-shelf blood bank-based or commercially produced reagents are likely to result in broader accessibility and possible manufacturing cost reduction of these cell products, and will open new therapeutic prospects for vulnerable and critically ill immunocompromised patients.